IDENTIFIKASI BAKTERI SALMONELLA SP DAN JUMLAH TOTAL KONTAMINAN BAKTERI COLIFORM PADA IKAN KEMBUNG (Scomber sp) YANG DIJUAL DI PASAR INPRES DAN OEBA - Ni Sri Yuliani; Ewaldus Wera; Petrus Malo Bulu (Partner, 2009)
Bacteria Identification Salmonella Sp And Full Scale Kontaminan Bacteria Coliform In Puffed Up Fish (Scomber Sp) That Sold At Inpres And Oeba Market. This study was about identification of salmonella bacteria and the total contaminant of colliform bacteria in kembung fish/ scomber sp that was sold in Inpres and Oeba Traditional Market. This study had been conducted for about 7 month in Kesmavet Laboratory, UPTD P2H Oesapa. Fifteen samples were taken randomly in each market, so that the total ofÂ  the sample were 30. The variables, which observed, were salmonella bacteria contaminant and the counting of colliform in kembung fish and physical observationof the fish. The data, which was collected from the results of examination and observation, were then analyzed descriptively. The result of the study showed that the total contaminant of colliform bacteria was 36 X 105 sel gram -1 in Inpres Market and 72 X 105 sel gram in Oeba Market, while there was no sign of Salmonella sp presents. This character was observed onmedia of XLD Agar, TSI Agar and LIA Agar so that the growth of bacteria colonizes in Inpres Market as well as in Oeba Market were prohibited. Key Words. : Kembung Fish, Contaminant, Colliform and Salmonella Bacteria